The Complexity of the Transition in Combat Operations and Potential Solutions to Streamline the Process - Claudiu Valer NISTORESCU (Bulletin of "Carol I" National Defense University)
The contemporary armed conflicts that have recently taken place in Ukraine, the Gaza Strip, and Nagorno-Karabakh serve to illustrate the inherent difficulties associated with combat operations. Despite the high degree of transparency on the battlefield, the nature of the conflict, characterized by friction, uncertainty, violence, and high lethality, underscores the pivotal role of the human factor. The operational process remains primarily driven by human decision-making, with the constant planning, preparation, execution, and evaluation of military operations shaped by the human decision-making process. In this context, the transition during combat operations is identified as one of the most challenging processes, particularly when unanticipated. The lessons learned from past conflicts indicate that the inherent risks associated with a period of change, the mental pressure, and the increased possibility of experiencing a decisive defeat have a multidimensional impact on both the decision-making process and the execution of the operation. In light of the sensitivity of the transition in combat operations, the analysis seeks to identify the principal vulnerabilities and risks inherent to the process, the triggers and indicators that signal its necessity, as well as a series of solutions to enhance its efficiency. The scientific approach is qualitative and empirically oriented, with a focus on examining the impact of new technologies and weapon systems on the conduct of combat operations.